How does justice matter in achieving buyer-supplier relationship performance? - Liu, Y.; Huang, Y.; Luo, Yadong; Zhao, Y. (Elsevier BV, 2012)
This study presents an analysis exploring how four types of justice (distributive, procedural, interpersonal, and informational) influence dyadic relationship performance in the buyer-supplier context. Underpinned by loose coupling theory, we build a mediating framework in which we propose that a high level of justice (or fairness) as mutually perceived by both parties drives buyer-supplier relationship performance through bolstered coupling links in mutual knowledge sharing, continuous commitment, and relationship investment. Our survey of 216 paired manufacturers (suppliers) and distributors (buyers) in China generally supports this argument, leading to a conclusion that justice is not a direct determinant of buyer-supplier performance but a critical conduit that nourishes mid-range coupling behaviors, which in turn promotes a successful relationship. Based on findings from this study, firms are encouraged to endorse all four kinds of justice in managing supply chain relationships. However, when constrained by resources, the recommendation for managers is to focus on achieving a high level of perceptual convergence on procedural justice and informational justice with the exchange partner, because mutual perceptions of procedural and informational justice have the strongest effects on coupling behaviors and buyer-supplier relationship performance.